Petrogenesis of the Late Oligocene Takht batholith, Southeastern Iran: Implications for the Diachronous Nature of the Arabia–Eurasia Collision - Pang, Kwan-Nang; Fazlnia, Abdolnaser; Ji, Wei-Qiang; Jamei, Susan; Jafari, Amin (Frontiers in Earth Science, 2020)
Zircon U-Pb age, mineral compositional, elemental and Sr-Nd isotopic data are documented for intermediate to felsic rocks in the Takht batholith, a Late Oligocene igneous complex in the southeastern segment of the Urumieh-Dokhtar belt, Iran, to investigate magma genesis in the context of regional tectonics. A large part of the magmatic belt formed by northward subduction of the Neotethys before the Arabia-Eurasia continental collision. Zircon U-Pb age data indicate the batholith crystallized at ~25 Ma, an age consistent with previous results. Geochemical data indicate that the rocks share features typical of calc-alkaline magmas and I-type granitoids. The least evolved magma inferred from the data has basaltic andesite composition, consistent with either of the following origins: (i) a partial melt of the mantle followed by differentiation, or (ii) a partial melt of the lower crust. With increasing SiO2, (87Sr/86Sr)25 Ma increases from 0.7053 to 0.7073, and εNd25 Ma decreases from –0.3 to –2.9, consistent with increasing effects of assimilation–fractional crystallization, although processes such as magma mixing and melting of heterogeneous source rocks cannot be entirely ruled out. Aluminum-in-hornblende thermometry indicates that the batholith might have emplaced at ~6.5 km or shallower paleo-depths. Moho depth proxies Sr/Y and (La/Yb)N yield crustal thickness of ~20–30 km, showing no evidence for magma processing within thick crust. Overall, our results indicate that the Takht batholith is a Cordilleran-type batholith formed beneath a continental or transitional arc of normal crustal thickness. This is consistent with the notion that Arabia and Eurasia have collided in a diachronous manner, propagating from the northwest to the southeast since the Late Eocene–Earlty Oligocene.